2017
DOI: 10.1007/s00228-017-2388-y
|View full text |Cite
|
Sign up to set email alerts
|

Measuring medication adherence in older community-dwelling patients with multimorbidity

Abstract: In total, 31% of older patients with multimorbidity were non-adherent to their medication but adherence levels varied across treatment categories and chronic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 36 publications
1
35
1
2
Order By: Relevance
“…Furthermore, this study found that people predominantly constituted priorities by targeting individual conditions that impact a lot, but the potential effects of the prioritisation were not identified. (Kim, Bennett, Wallace, Fahey, & Cahir, 2018), medication beliefs (Schüz et al, 2011), fragmented care (Green, Hawley, & Rask, 2007) and synergistic effects between chronic conditions (Calderón-Larrañaga et al, 2019). Participants in this study did not report issues of managing multiple prescriptions nor adverse effects.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, this study found that people predominantly constituted priorities by targeting individual conditions that impact a lot, but the potential effects of the prioritisation were not identified. (Kim, Bennett, Wallace, Fahey, & Cahir, 2018), medication beliefs (Schüz et al, 2011), fragmented care (Green, Hawley, & Rask, 2007) and synergistic effects between chronic conditions (Calderón-Larrañaga et al, 2019). Participants in this study did not report issues of managing multiple prescriptions nor adverse effects.…”
Section: Discussionmentioning
confidence: 95%
“…These explanations might indicate that people misunderstood their health regarding MCCs and an inability to participate in disease self‐management (Pages‐Puigdemont et al, ). Key reasons for nonadherence to treatments among MCCs population are varied, including differences in clinical variables (Kim, Bennett, Wallace, Fahey, & Cahir, ), medication beliefs (Schüz et al, ), fragmented care (Green, Hawley, & Rask, ) and synergistic effects between chronic conditions (Calderón‐Larrañaga et al, ). Participants in this study did not report issues of managing multiple prescriptions nor adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…The most common conditions were hyperlipidemia, cerebrovascular disease, and heart disease. 28 The majority of the 15 family physician practices taking part in the study had above average deprivation in their catchment area (median deprivation score 2.95; range −1.04 to 4.86). 21…”
Section: Study Populationmentioning
confidence: 99%
“…There is also some evidence that not only the number of morbidities but the types of morbidities influence medication adherence. 12 Kardas et al 7 found significant variability in primary nonadherence across therapeutic areas, drug classes, and individual drugs. In recent years, there has been a rapid increase in the prevalence of multimorbidity and polypharmacy, presenting significant challenges for monitoring and supporting medication adherence.…”
Section: How To Citementioning
confidence: 99%
“…There is some evidence of a threshold effect for the relationship between number of concurrent medications and medical conditions and adherence. 12 Adherence has been shown to initially increase, followed by a decrease as the number of morbidities and/or medications increases. There is also some evidence that not only the number of morbidities but the types of morbidities influence medication adherence.…”
Section: How To Citementioning
confidence: 99%